Ultrasonographic Morphologic Changes of the Central Aponeurosis of the Rectus Femoris Muscle in Individuals With Knee Osteoarthritis. Issue 3 (September 2016) - Takahashi, Yusuke; Okada, Kyoji; Saito, Akira; Saito, Isao; Kinoshita, Kazuo; Wakasa, Masahiko; Sato, Hiromichi; Shibata, Kazuyuki
Abstract : Abstract: The aim of this study was to clarify the morphologic characteristics of central aponeurosis (CA) of the rectus femoris (RF) muscle in individuals with medial knee osteoarthritis (OA). Forty legs in 26 individuals with medial knee OA (OA group), 41 legs in 21 elderly individuals (elderly group), and 40 legs in 20 young individuals (young group) were investigated. We measured the following 4 parameters: (1) ratio of CA length, expressed as the percentage of RF length; (2) CA morphologic type (curved, straight, S-shaped, or irregular); (3) CA direction, defined as the direction of the line from the anterior to posterior ends of the CA (lateral or medial); and (4) intercondylar distance (ICD). Ratio of CA length in the OA group was significantly smaller than that in the other 2 groups. The curved CA type was significantly more frequent in the young group than in the other 2 groups. The irregular type was observed in only 7 legs in the OA group. In the young group, CA direction was classified as medial in all cases. Laterally directed CA was observed only in the OA and elderly groups. Within the OA group, ICD in laterally directed CA was significantly larger than that in medially directed CA. Central aponeurosis observed in the RF muscle in individuals with medial knee OA is shorter and sometimes shows an irregular shape. Laterally directed CA is associated with increased ICD in knee OA. Attention should be given to the tendon-aponeurosis complex in individuals with medial knee OA.